Formação continuada em serviço : contribuições para a prática pedagógica de língua portuguesa nos anos finais do ensino fundamental - ALVES, Carlos Eduardo Barbosa (2017)
The challenges posed by knowledge upgrades and socioeconomic transformations require a new look at school educational actions. Therefore, pedagogical practices need to be rethought to be also connected with these changes. In this sense, continuing education in service emerges as an action that helps the teacher to update his knowledge and adopt methodological positions. Based on this perspective and, therefore, recognizing its importance, the present study has as general objective to analyze the effects of the continuous training in the practice of Portuguese Language teachers, reflecting on the offer of these formations and the effectiveness, or not, in the classroom of the concepts conveyed in them. For this, we are based on authors of the area of teacher training (BEHRENS, 2005, 2007; OLIVEIRA, 2012; IMBERNÓN, 2009); theorists and researchers of the Portuguese language teaching (KOCH, 2009; TRAVAGLIA, 2008; KLEIMAN, 2002,2011; MARCUSCHI, 2002; ANTUNES, 2003,2006; GERALDI, 1997; MENDONÇA, 2006; BEZERRA & REINALDO, 2013) official teaching: PCN (1997, 1998) and Curricular Parameters of Pernambuco (2012). We applied the questionnaire for teacher and trainer and videogravation of classes and continuing training. These two methodological procedures were mediated by discourse analysis concepts, namely: interdiscourse and discursive heterogeneity (MAINGUENEAU, 2008; AUTHIER-REVUZ, 1990,2004). Thus, it was possible to verify that the continuing formations promoted are satisfactory from a theoretical and methodological point of view, since they are in tune with the current discussions about language teaching. However, they require adjustment in the configuration aspects of the offer (periodicity, duration and format), as there are difficulties of effectiveness of what is discussed in the formative moments, since there were discrepant language practices among the official guidelines for language teaching. Finally, it was possible to understand that continuing education can contribute to the construction of an innovative practice, but teachers must also be committed to updating their practices in face of new educational requirements.